تطبيقات تأمين برودنشيال الشرعي في نظر الفقه الإسلامي (The Application of Prudential Syariah Insurance) - Hadziq, Sholihien (2013)
This simple thesis discusses about Application of Prudential Syariah Insurance in Prudential Syariah Insurance Corporate. Insurance, either syariah or confentional is new practice of business which unknown in early period of Islam society, so we haven't found much papers and books or references which discuss about it except in the latest period, but by quickly growing of insurance practice in economic life, we can find many insurance practices in our life activities, therefore, the insurance now is becoming our daily needs. The development of syariah insurance practice in Indonesia grows together with development of insurance business practice in company activities in the end of nineteenth century. The first syariah insurance application was Indonesian Syariah Takaful Corporate, after that, Mubarokah Insurance Corporate which is followed by many Syaraih Insurance Corporates, including Syariah Prudetial Insurance. Unfortuntely, the fast growing of development of this syariah insurance corparetes isn't followed by insurance knowledge in muslim society, so they didn't understand what is syariah insurance, how to apply syariah insurance, therefore many muslim society can't make difference between syariah insurance and conventional insurance. So, it's important for muslim society to know and learn the application of this insurance and understand the difference between syariah insurance and conventional insurance and they also know the Islamic law both, till they have enough knowledge about this insurance and can make decision correctly about it. Growing of the many insurances in Indonesia, they are very important for muslims society to know the real form of applicatation of syaraiah insurance, because there are many muslims who doubt and don't understand about it. Based on the above reasons, this thesis which discusses syariah inserance application is very important and very useful for muslim society, and may become the answers for their questions about this application and islamic low of this insurance.